Pengaruh Fraksi Volume Pada Komposit Serat Lapisan Batang Pisang Kepok Dengan Perlakuan Asap Cair Terhadap Kekuatan Tarik - Kusuma, Sultan Chandra; Yuliyanto , Yuliyanto; Dharta, Yuli (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Synthetic fiber composite materials such as glass fiber, aramid and carbon fiber have good mechanical properties, but cause environmental pollution because they cannot be recycled. Because of this, many researchers are making composites with natural fibers. The advantages of natural fibers include: lower price, easy processing, reduced CO2 emissions, and specific strength meets application requirements. Composites are materials composed of a mixture of more than two different main elements. Composites have the advantages of light weight, higher strength, and corrosion resistance. This study applies the full factorial design method, which will look at the effect of the composite ratio (volume fraction and between fiber layers) on tensile strength. The purpose of this research is to determine the effect of variations in volume fraction and fiber layers of kepok banana stems on tensile strength. So that it can be used as an alternative material for making SNI helmets. This study used variations in volume fractions of 10%, 15%, and 20% and variations in fiber layers of 3, 4, and 5 kepok banana stems. Liquid smoke soaking time was 60 minutes. The average value of the maximum tensile test in the 4th layer, 10% volume fraction of fiber with a value of 42.76 Mpa and the minimum average value in the 3rd layer using 10% volume fraction of fiber with a value of 30.06 Mpa.